Hexahelix Collaboration: Street Vendor Arrangement To Achieve Cleanliness, Order And Beauty - Beby Thaharah; Aprilianti Noer Indah Suci; Moh. Taufik Hidayat; Aghnia Dian Lestari (Al-Makki Publisher, 2024)
Hexahelix Collaboration on Street Vendor Arrangement for Occupying K3 (kebersihan, ketertiban, keindahan). Street vendors are often considered to interfere with urban K3 (kebersihan, ketertiban, keindahan) because there are still many street vendors who sell on the shoulder of the road which causes congestion on the road and disrupts road order, there are still many street vendors who pay less attention to cleanliness in the environment they sell which causes a lot of piles of garbage on the side of the road. This makes the beauty value of the urban area go down. The problem of street vendors is a problem that must be solved together and requires hexahelix collaboration between Government, Academics, Media, Business, Community, and Financial Institutions. The purpose of this research is to find out the collaboration process between stakeholders involved in the hexahelix collaboration of street vendors' arrangement to realize K3 (kebersihan, ketertiban, keindahan). This research uses a descriptive qualitative approach method with field studies, observation, documentation, and interviews. The results of this research show that there is no direct collaboration between the actors contained in the Hexahelix concept.